2011
DOI: 10.4028/www.scientific.net/amr.233-235.2011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Catalytic Efficiency of Ti-SBA-15 Mesoporous Materials

Abstract: Ti-SBA-15 mesoporous materials were directly synthesized via a hydrothermal process and characterized by using nitrogen adsorption-desorption measurements, X-ray diffraction, scanning electron microscopy, transmission electron microscopy, diffuse reflectance ultraviolet-visible spectroscopy, and infrared ray spectroscopy. The effect of synthesis temperatures on the structure and catalytic efficiency in epoxidation of cyclohexene was discussed in details. The results showed that the optimal temperature was 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results indicated that Ti-SBA-15 materials retained the ordered mesoporous structure of SBA-15. Moreover, compared with pure SBA-15, there was a shift towards lower angles for the characteristic peaks of the Ti-SBA-15 due to the fact that the Ti-O bond is longer than that of Si-O [5]. Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The results indicated that Ti-SBA-15 materials retained the ordered mesoporous structure of SBA-15. Moreover, compared with pure SBA-15, there was a shift towards lower angles for the characteristic peaks of the Ti-SBA-15 due to the fact that the Ti-O bond is longer than that of Si-O [5]. Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, it is of great importance to introduce active sites in the mesopore frameworks. To date, much effort has been made to the study of the catalytic efficacy of mesoporous molecular sieves containing titanium [5][6][7]. The results showed that the reaction presented a high velocity during the 1st hours and cyclohexene epoxide was the main product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation